Progressive Bulbar Palsy (PBP) or Bulbar Onset MND: “A Case Report” - Sagar S. Bhovare; Akhataribano S. Sayyad (Journal of Pharmacy and Bioallied Sciences)
A patient with enhancing bulbar palsy, a type of efferent neuron disease that causes hypertrophy and twitching of the tongue’s musculature, dysphagia, dysarthria, and an excessive buildup of secretions, is described. Enhancing bulbar palsy is a degenerative disorder of the efferent nuclei in the medulla. The patient may consult a dentist at first. Clinicians must possess knowledge regarding the telltale signs and symptoms of this terminal illness to promptly refer patients for neurologic evaluation and initiate appropriate symptomatic treatments.